METODE MEMAHAMI SUMBER AJARAN ISLAM; METODOLOGI PENDIDIKAN ISLAM (Studi Kasus Masyarakat di Kota Medan) - Meliastaras Surbakti; Muhammad Bintang Chadavi (Adabiyah Islamic Journal, 2023)
Islamic education is education that is carried out based on the pattern of Islamic teachings. Because Islamic teachings are based on the Qur'an, the Sunnah, the opinions of scholars and historical heritage, Islamic education is also based on the Qur'an, the Sunnah, the opinions of scholars and the historical heritage. The purpose of this study is to analyze how the development of community Islamic education in big cities such as Medan. This study uses a qualitative type, because it will describe, understand, and interpret data in the field. This research uses a case study approach. A case study is a research strategy, an empirical study that investigates a phenomenon in a real-life setting. The results of the study can be concluded that the existence of Islamic education in the community in big cities such as the city of Medan has a very large influence on the development and character of children's growth and development, children who live in rural areas will have a much better Islamic education than children who live in rural areas. big cities like Medan.